Ultrafast gas chromatography method with direct injection for the quantitative determination of benzene, toluene, ethylbenzene, and xylenes in commercial gasoline - Miranda, Nahieh Toscano [UNESP]; Sequinel, Rodrigo [UNESP]; Hatanaka, Rafael Rodrigues [UNESP]; de Oliveira, José Eduardo [UNESP]; Flumignan, Danilo Luiz [UNESP] (Wiley, 2017)
Benzene, toluene, ethylbenzene, and xylenes are some of the most hazardous constituents found in commercial gasoline samples; therefore, these components must be monitored to avoid toxicological problems. We propose a new routine method of ultrafast gas chromatography coupled to flame ionization detection for the direct determination of benzene, toluene, ethylbenzene, and xylenes in commercial gasoline. This method is based on external standard calibration to quantify each compound, including the validation step of the study of linearity, detection and quantification limits, precision, and accuracy. The time of analysis was less than 3.2 min, with quantitative statements regarding the separation and quantification of all compounds in commercial gasoline samples. Ultrafast gas chromatography is a promising alternative method to official analytical techniques. Government laboratories could consider using this method for quality control.
Keywords: direct injection; gas chromatography; gasoline; quality control